Wanderers: Social history of childhood in Antioquia 1892-1936 (2021)
This book presents a social history of childhood in Antioquia (Colombia) between 1892 and 1936. It describes the place that children used to have in Antioquia´s society. The analysis of the spaces children inhabited, their behavior, and daily practices made visible a diverse population that fulfilled different roles. Children were not kept apart from adults’ world they usually were integrated into society. But children had a preference for wandering and inhabiting spaces that allowed them to be away fromadults.These freewheeling children were presumed to be a social nuisance, then confronting their laziness, limiting their mobility, and locking them up emerged as a viable policy. The creation and consolidation of the institution Casa de Menores y Escuela de Trabajo of Antioquia was the mostrepresentative strategy of these new policies. The institution leadership implemented actions to stop children behaving like children and to carve them into what society expected them to be, docile bodies of production.But children did not always react submissively to adults’ strategies of confinement and body domestication. They were independent, creative, and bold in their tactics for circumventing those strategies. The analysis of the tactics used for getting out of the places where they were proscribed and confined showed the complexity of the experiences they had.The experience of childhood can be better understood, not only by focusing on its negativity, on what they lack, or it is missing, but from its positivity; childhood took as a symbol of new beginnings and the latent possibility of transformation.The problems to fully comprehend what place in society children should occupy are related to the fact that adults impose them a role without taking their experiences into account. Adults’ understanding of children’s experiences in social life will enrich their own, opening new ways for improving the complicated relationship that children and adults have.